PRAKTEK DINASTI POLITIK PADA PILKADA SERENTAK JAWA TENGAH TAHUN 2020 - Agus Riyanto; Yulita Nilam Fridiyanti; Joko Juli Prihatmoko (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
This article aims to explain the practice of political dynasties in the 2020 Central Java simultaneous regional elections. By understanding the phenomenon holistically using qualitative description methods, the results of the research show that there are 10 (ten) candidates who are indicated to be related to political dynasties in the 2020 Central Java simultaneous regional elections. The existence of political dynasties This cannot be separated from three factors: first, regional election regulations, especially after the decision of the Constitutional Court (MK) Number 33/PUU-XIII/2015; second, the failure of political parties to produce cadres; third, society's permissive attitude towards the practice of dynastic politics. Political dynasties in the implementation of simultaneous regional elections in Indonesia will continue in the future until the emergence of